Islamization of Economics in Pakistan: Analyzing the Weaknesses in Muftī Taqī ʿUsmānī’s Response to Capitalism - Zain Razzaq (El-Barka Journal of Islamic Economics and Business, 2026)
This study addresses a significant gap in the literature on the Islamization of economics in Pakistan by critically examining Muftī Taqī ʿUsmānī’s conception of capitalism and his proposed strategy for its Islamization. The purpose of the paper is to analyze how capitalism is conceptualized in ʿUsmānī’s writings and to assess his proposed Islamic alternative to capitalism. Methodologically, it employs qualitative critical textual analysis of two of ʿUsmānī’s key works—“Islam aur Jadīd Maʿīshat-o-Tijārat” and “An Introduction to Islamic Finance”. The findings indicate that ʿUsmānī treats capitalism primarily as an economic system rather than as a broader socio-cultural and political order. This perspective leads him to propose reforming or Islamizing capitalism through the removal of specific practices, particularly interest-based financial mechanisms. However, the analysis demonstrates that Islamizing capitalism is fundamentally impossible, as its structures and values are incompatible with Islamic principles. The study develops a theoretical analysis by distinguishing capitalism as a totalizing system that structures social, cultural, and political life from its narrower conception as a purely economic system. It also considers the implications of ʿUsmānī’s focus on the economic dimension, showing how Islamization frameworks that address primarily economic aspects may overlook the broader systemic character of capitalism.